Research on the Aerodynamic–Propulsion Coupling Characteristics of a Distributed Propulsion System - Xiaojun Yang; Tao Liu; Wei Jia (Applied Sciences)
In recent years, the distributed propulsion system has received extensive attention due to its advantages such as high propulsion efficiency, low noise, high safety redundancy, and good flexibility and maneuverability. However, the interaction between the internal and external flow can limit the aerodynamic performance of the ducted fan. To investigate the influence of the internal and external flow interaction on the aerodynamic–propulsion coupling characteristics of the distributed propulsion system, an over-wing symmetric configuration with five distributed ducted fans was constructed, and numerical simulations were performed using a method based on the body force model. Results show that as the flight Mach number increases, the lift obtained by the wing increases, while the stall angle of attack decreases, and the stall angle of attack at a Mach number of 0.5 is reduced by 15° compared with a Mach number of 0.2. At large angles of attack, the edge fans have the strongest ability to resist airflow separation, while the middle fan has the weakest ability to resist airflow separation, and its fan performance index drops the fastest. When the Mach number is 0.4, the mass flow rate and thrust of the middle fan are reduced by 16% and 28%, respectively, compared with those when the Mach number is 0.2. The higher the flight Mach number, the larger the intake distortion degree of the ducted fans. The middle fan is most affected by total pressure distortion and least affected by swirl distortion, whereas the edge fans are least affected by total pressure distortion and most affected by swirl distortion.